The effect of IQ vs. EQ on knowledge management and innovation - Noordin, Mohamad Fauzan; Abd Karim, Zulkarnain (IEEE, 2014)
The debate over the importance of IQ vs. EQ on people’s performance has been long disputed between researchers. One of the areas that it could influence is on knowledge management (KM) and innovation which are highly dependent on the people. Nevertheless, studies on KM and innovation are mostly focusing on the management or organizational level issues. There is a need to study this relationship at the individual level to see how individuals influence their organizational KM and innovation. This study aims to compare the effect of IQ vs. EQ on KM and innovation. Survey questionnaires are used to measure IQ and EQ, respondents’ KM processes involvement and perception on their innovation performance. Partial least square (PLS) analysis is used in the analyses to determine the relationship between IQ, EQ, KM processes and organizational innovation. Results indicate that EQ influenced KM and innovation significantly, but this is not the case for IQ.